Making Cinelandia : American Films and Mexican Film Culture before the Golden Age - Serna, Laura Isabel, 1971- (Book collections on Project MUSE., 2014)
In the 1920s, as American films came to dominate the country's cinemas, many of Mexico's cultural and political elites feared that this "Yanqui Invasion" would turn Mexico into a cultural vassal of the United States. In Making Cinelandia, Laura Isabel Serna contends that Hollywood films were not simply tools of cultural imperialism. Instead, they offered Mexicans on both sides of the border an imaginative and crucial means of participating in global modernity, even as these films and their producers and distributors frequently displayed anti-Mexican bias. Before the "Golden Age."